Whole-body vibration exposure on earthmoving equipment operators in construction industries. Issue 1 (1st January 2018) - Akinnuli, B.O.; Dahunsi, O.A.; Ayodeji, S.P.; Bodunde, O.P.
Abstract: Operators of Earthmoving Equipment (EME) are daily exposed to certain Whole-body vibration (WBV) dosage, exceeding the recommended values. In this study, the WBV experienced by operators of EME used in construction industries were measured using a tri-axial accelerometer (GCDC X16-4 3-Axis, G-Force Data logger, ±18 g acceleration range). These measurements were taken on the seats and floors of EME in x, y and z directions. Weighted root-mean-square accelerations ( A RMS ), Vibration dose values (VDVs), Crest Factors (CFs), time to reach health guidance caution zone (HGCZ) which are important evaluation parameters specified by the International Organiization for Standardization (ISO) were determined for each equipment used in the study. The values of the CF were mostly found to be greater than 9 indicating presence of multiple shocks during the operation of the equipment studied. The research revealed higher magnitude of acceleration in the vertical, z-axis, some very few are within the HGCZ ( A RMS < 0.47 and >0.93 m/s 2 ; VDV < 8.5 and >17 m/s 1.75 ) specified by ISO, also accelerations on x- and y-axes fell within the HGCZ and very few below the lower limit 0.47 m/s 2 . The values of the A RMS and VDV were also compared with the European Parliament Directive 2002/44/EC (A(8) < 0.5 and >2.5 m/s 2 ; VDV < 9 and >21 m/s 1.75 ). Appropriate technology should be adopted to minimize the WBV reaching operators, and/or appropriate maintenance routine should be maintained in EMEs to combat the health risks associated with WBV.